The Franciscan Invention of the New World - McClure, Julia. author. aut Link
XIII, 229 p.
Keywords: This book examines the story of the ‘discovery of America’ through the prism of the history of the Franciscans, a socio-religious movement with a unique doctrine of voluntary poverty. The Franciscans rapidly developed global dimensions, but their often paradoxical relationships with poverty and power offer an alternate account of global history. Through this lens, Julia McClure offers a deeper history of colonialism, not only by extending its chronology, but also by exploring the powerful role of ambivalence in the emergence of colonial regimes. Other topics discussed include the legal history of property, the complexity and politics of global knowledge networks, the early (and neglected) history of the Near Atlantic, and the transatlantic inquisition, mysticism, apocalypticism, and religious imaginations of place.